1977
DOI: 10.2466/pr0.1977.40.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Humorous Responses to Embarrassment

Abstract: Humor is a technique that is frequently used to restructure an interpersonal communication when embarrassment has broken down communication patterns. In an embarrassing interaction, it is expected that more humor will be used between persons of relatively equal status than when people are of unequal status and that more humor will be initiated by a person of relatively higher status than by a person of lower status. It is hypothesized that more humor will be used when interactants anticipate future interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Other similar studies of laughter have a high intercoder correlation for laughter (e.g. 0.99 for Fink & Walker 1977).…”
Section: Previous Researchmentioning
confidence: 94%
“…Other similar studies of laughter have a high intercoder correlation for laughter (e.g. 0.99 for Fink & Walker 1977).…”
Section: Previous Researchmentioning
confidence: 94%
“…Studies using observational methods (e.g., Campbell et al, 2008) have also concluded that aggressive humor has negative relational consequences, which suggests that this limitation did not result in inconsistent findings. Furthermore, the processes identified here may be part of a larger causal sequence involving humor and embarrassment (Fink & Walker, 1977). Future work should employ observational methods to explore how one partner responds to another's aggressive joking in public.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Humor allows an embarrassing actor to cope with embarrassment by implicitly acknowledging blameworthiness, releasing situational tension, and overcoming a lapse in social competence with a display of social competence (Edelmann, 1985;Fink & Walker, 1977). Both laughter and jokework are considered helpful forms of humor.…”
Section: Remedial Strategiesmentioning
confidence: 97%